EFFICACY AND SAFETY OF LUBIPROSTONE FOR FUNCTIONAL CONSTIPATION IN CHILDREN: A SYSTEMATIC REVIEW - Dilokthornsakul, Witoo; Sukwuttichai, Pattarapan; Taesotikul, Suthinee; Nimworapan, Mantiwee; Permsuwan, Unchalee; Yadee, Jirawit; Dilokthornsakul, Piyameth (Thai Bulletin of Pharmaceutical Sciences, 2023)
Pediatric functional constipation (PFC) is an important gastrointestinal disease in children. Oral and rectal laxatives have been recommended for treating PFC; however, almost half of the patients did not fully recover after 6 – 12 months of treatment. Lubiprostone is an alternative to treat PFC. However, the efficacy and safety of lubiprostone have not been summarized. This study aimed to summarize the efficacy and safety of lubiprostone for PFC. A systemic review was conducted in PubMed, Embase®, and Cochrane CENTRAL from their inception to August 2022. Studies examining the efficacy or safety of lubiprostone compared to placebo or different dosages of lubiprostone were eligible. The primary efficacy outcome was the number of responders according to spontaneous bowel movement (SBM), while the serious adverse event was the primary safety outcome. A qualitative summary was performed to summarize the evidence. A total of three articles with 1,264 patients met the inclusion criteria. Of those, one article was a randomized controlled trial (RCT) with an open-label, long-term extension and two studies were quasi-experimental. All included studies reported serious adverse events but only two studies reported SBM. The RCT indicated that 12 micrograms of lubiprostone twice daily (BID) or 24 µg BID had no statistical difference in terms of treatment response than the placebo (relative risk [RR]= 1.32; 95% confidence interval (CI) 0.89 to 10.97, p=0.22). However, when sub-grouped, lubiprostone 12 µg BID had a higher chance of being responsive than the placebo (RR= 1.89 [1.19 to 3.00], p=0.007), while lubiprostone 24 µg BID did not have a higher chance of being response than the placebo (RR= 1.12 [0.73 to 1.72], p=0.60). A non-RCT study demonstrated significant improvement of average SBM from the baseline for lubiprostone 12 µg once daily (OD), 12 µg BID, and 24 µg BID at week 4, however no significant difference among the doses was observed. No difference in serious adverse events between lubiprostone and the placebo was found. In conclusion, lubiprostone showed potential efficacy for treating children with functional constipation without any serious adverse events.